Analisis Buku Teks Durus Al-Lughah Al-Arabiyyah Kelas Ⅲ SDIT El-Haq Buduran Sidoarjo - Sugiharti, Susi; Hikmah, Khizanatul (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
Textbook analysis is very important to do. It aims to assess the quality of the book. So, with the analysis of text nuclei can be found the advantages and disadvantages for improvement. This research is a qualitative research on content analysis of the Durus Al-Lughah Al-Arabiyah Class III textbook SDIT EL-Haq Buduran Sidoarjo from the aspect of material presentation and language. In data collection, apart from the primary data of the textbook itself, it is also supported by secondary data from observations, interviews and documentation. In analyzing the data using instruments issued by the Ministry of Religion. The results showed that from the feasibility aspect of presenting the material, it was classified as good with a percentage of 69% which indicated that there were 31% that needed to be improved from the aspect of presenting the material. While the appropriateness of textbooks from the linguistic aspect is 68% which indicates that there is still much that needs to be done in terms of the linguistic aspects of the book.